Radical History in Australia: A Model for Canada? - Friesen, Gerald (Labour / Le Travail, 1991)
The article reviews several books edited by Verity Burgmann and Jenny Lee including "A People's History of Australia Since 1788: Constructing a Culture," "A People's History of Australia Since 1788: Staining the Wattle," and "A People's History of Australia Since 1788: Making a Life."
Keywords: BOOKS – Reviews; BURGMANN; Verity; LEE; Jenny; Nonfiction; PEOPLE'S History of Australia Since 1788: Constructing a Culture; A (Book); PEOPLE'S History of Australia Since 1788: Making a Life; A (Book); PEOPLE'S History of Australia Since 1788: Staining the Wattle; A (Book)